Physical activity, resilience, emotions, moods, and weight control, during the COVID-19 global crisis - Sima Zach; Javier Fernandez-Rio; Aviva Zeev; Miki Ophir; Sigal Eilat-Adar (BMC, 2021)
Abstract Objectives This study aimed at exploring the relationships between physical activity, weight control, and psycho-social aspects of the COVID-19 lockdown, which have characterized the Israeli population's behavior during the COVID-19 global crisis. Design Cross-sectional survey research. Methods Participants included 1855 men and women aged 18 and above, from different regions in the country and representing different sectors. They were recruited through the social media in a "snowball" sampling, and filled out a self-administered six-part survey: Demographic background, the International Physical Activity Questionnaire (IPAQ), the positive and negative affect scales (PANAS), the Conor and Davidson resilience scale, a questionnaire for measuring depressive symptoms, and questions regarding weight change based on the Israeli National Health and Nutrition (MABAT) survey. Results Routine physical activity (PA) was reported by 76.3% of the participants before the lockdown, 19.3% stopped exercising during this period, and 9.3% began exercising during the lockdown. The participants who were physically active during the lockdown period reported a higher level of resilience and positive feelings, and a lower level of depression, compared with those who were not physically active. People who were physically active during the lockdown maintained their weight compared with those who were inactive. Concerning weight change, 44.8% of the respondents maintained their weight, and a higher percentage of people reported weight gain than those who reported weight loss. Conclusions Continuous PA before and during the COVID-19 lockdown were associated with higher resilience and positive emotions, and depressive symptoms, in people aged 18 and above. Although a causal link cannot be established, in light of the results of the present study, encouraging physical activity may contribute to improving mental health and a sense of self-efficacy, as well as to maintaining weight during a crisis.